2010
DOI: 10.1016/j.ejmech.2010.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Structural determinants of resveratrol for cell proliferation inhibition potency: Experimental and docking studies of new analogs

Abstract: Resveratrol is the subject of intense research because of the abundance of this compound in the human diet and as one of the most valuable natural chemopreventive agents. Further advances require new resveratrol analogs be used to identify the structural determinants of resveratrol for the inhibition potency of cell proliferation by comparing experimental and docking studies. Therefore, we synthesized new trans/(E)- and cis/(Z)-resveratrol - analogs not reported to date - by modifying the hydroxylation pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 37 publications
(51 reference statements)
5
52
0
Order By: Relevance
“…1). This is supported by the similar antitumor potency of pterostilbene, which shares the 3,5-dimethoxy groups, and the published reports that methoxylated resveratrol analogs have increased activity against cell viability compared with the parent compound (Mazué et al, 2010). However, pterostilbene had a moderate effect on Stat3 tyrosine705 phosphorylation compared with Cmpd1, underscoring the differences in the underlying molecular mechanisms between the two compounds.…”
Section: Discussionsupporting
confidence: 46%
“…1). This is supported by the similar antitumor potency of pterostilbene, which shares the 3,5-dimethoxy groups, and the published reports that methoxylated resveratrol analogs have increased activity against cell viability compared with the parent compound (Mazué et al, 2010). However, pterostilbene had a moderate effect on Stat3 tyrosine705 phosphorylation compared with Cmpd1, underscoring the differences in the underlying molecular mechanisms between the two compounds.…”
Section: Discussionsupporting
confidence: 46%
“…In most studies, trans isomers of stilbene derivatives enhanced the process of tubulin polymerization, while cis isomers -analogs of CA-4 promoted the process of depolymerization, inhibiting the formation of microtubules. Mazue et al [53] studied the anti-mitotic activity of a series of both cis-and trans-resveratrol analogs. Using a molecular docking method as a complement to experimental studies on the proliferation inhibition of the human colorectal tumor SW480 cell line, they showed that the cis configuration associated with the substitution of hydroxy groups with methoxy groups is crucial and increases inhibition efficacy.…”
Section: Resveratrol Analogsmentioning
confidence: 99%
“…The docked structures of cis-polymethoxy isomers overlap with the docked structure of CA-4 at the tubulin colchicine-binding site, while transpolymethoxy isomers do not fit CA-4. However, isomers of both conformations induced polyploidy resulting from the blocking of cell divisions at the mitosis level [53]. 3,4,4',5-tetramethoxy-trans-stilbene (MR-4; DMU-212; 3; Fig.…”
Section: Resveratrol Analogsmentioning
confidence: 99%
“…[30][31][32] To evaluate the substituted group effect of the benzoselenazole moiety in antiproliferative activity, we introduced a series of groups, including fluorine, chlorine and methoxy, into the C ring. In addition, to evaluate the steric effect of the stilbene backbone on the cytotoxic activity of the compounds, we changed the trans configuration of compound 6a to yield 9 (cis configuration).…”
Section: Introductionmentioning
confidence: 99%